The Environmental and Sustainable Factors on the Special Economic Zones Development - Suharman Hamzah; Daisy Pangemanan; Evi Aprianti (Civil Engineering Journal, 2023)
The process towards sustainability is indeed very complicated, given the increasing need of the population for infrastructure to support human activities. The objective of the study is to analyze the influence of environmental factors and their awful effects on infrastructure projects with sustainable construction models in special economic zones. The methodology used are mixed methods, combination of quantitative and qualitative approaches with the total respondent are 80 persons. The respondents involved are divided by company/institution, company’s qualifications, and stakeholders. The first validity shows that all factors have a value above 0.5, by using Fornell Lacker Criterion, it is found that the CDV value met the requirements from all variables involved. The validation was calculated by a cross-loading method called discriminant validity. After validity, it is continued to obtain model fit value and the final model fit is 0.568 means good model. The NFI value released was 56.8%. It means that the declared model was good enough to be implemented within sustainability in SEZs. This result supported the previous research, which stated that a sustainable construction model using a multi-criteria approach is a good model choice for the development of a sustainable construction model. Doi: 10.28991/CEJ-2023-09-02-06 Full Text: PDF